2015
DOI: 10.1109/lgrs.2014.2372875
|View full text |Cite
|
Sign up to set email alerts
|

Using a Multistructural Object-Based LiDAR Approach to Estimate Vascular Plant Richness in Mediterranean Forests With Complex Structure

Abstract: Artículo de publicación ISIA multistructural object-based LiDAR approach to predict plant richness in complex structure forests is presented. A normalized LiDAR point cloud was split into four height ranges: 1) high canopies (points above 16 m); 2) middle-high canopies (8-16 m); 3) middle-low canopies (2-8 m); and 4) low canopies (0-2 m). A digital canopy model (DCM) was obtained from the full normalized LiDAR point cloud, and four pseudo-DCMs (pDCMs) were obtained from the split point clouds. We applied a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…While these links sometimes allow good local estimates, the approach is hardly transferable in space and time and depends on calibration on the spot. The correlative approach was found to work in all major domains of remote sensing like multispectral remote sensing (e.g., Foody & Cutler 2003, 2006, Feilhauer & Schmidtlein 2009, Rocchini 2007, hyperspectral remote sensing (e.g., Laurin et al 2014) as well as active remote sensing or combinations (e.g., Camathias et al 2013, Higgins et al 2014, Lopatin et al 2015, 2016, Simonson et al 2012, Hernández-Stefanoni et al 2014. Reviews can be found for example in Wang et al (2010) and Rocchini et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…While these links sometimes allow good local estimates, the approach is hardly transferable in space and time and depends on calibration on the spot. The correlative approach was found to work in all major domains of remote sensing like multispectral remote sensing (e.g., Foody & Cutler 2003, 2006, Feilhauer & Schmidtlein 2009, Rocchini 2007, hyperspectral remote sensing (e.g., Laurin et al 2014) as well as active remote sensing or combinations (e.g., Camathias et al 2013, Higgins et al 2014, Lopatin et al 2015, 2016, Simonson et al 2012, Hernández-Stefanoni et al 2014. Reviews can be found for example in Wang et al (2010) and Rocchini et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…All the previous species richness estimations are based on lidar metrics related to vegetation height variations, habitat heterogeneity or topographic information, independently from the forest type under examination. Besides the indices useful in the studies already mentioned above (Ceballos et al, 2015;Hernandez-Stefanoni et al, 2014;Simonson et al, 2012), indices related to vegetation height and structural complexity were used by Lucas et al (2010), Lopatin et al (2015), and Wolf et al (2012); while altitude above sea level, standard deviation of slope and mean canopy height were the most important predictors in the Lopatin et al (2016) research.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of lidar for tree species richness estimation has been tested in an exiguous number of studies. Successful results were obtained in marsh, meadow and woodland habitats in Mississippi (Lucas et al, 2010), in Mediterranean forests (Lopatin et al, 2015;Lopatin et al, 2016;Simonson et al, 2012), where lidar also outperformed hyperspectral data for species richness estimation (Ceballos et al, 2015); and in two tropical forest cases (Hernandez-Stefanoni et al, 2014;Wolf et al, 2012). Lopatin et al (2016) argued that lidar can be used to derive three types of information that interacts with plant species richness: micro-topographical, macro-topographical and canopy structural information.…”
Section: Introductionmentioning
confidence: 99%
“…The PLSR linear multivariate model is useful for analysing datasets with many high dimensional and collinear predictors (Wold et al, 2001). The PLSR model creates orthogonal (uncorrelated) weight vectors by maximising the covariance between the explanatory and response variables while reducing the dimensionality of these x variables by sifting out the factors that explain the most information between all the x and y variables (Lopatin et al, 2015). …”
Section: Partial Least Squares Regression (Plsr)mentioning
confidence: 99%